THE STRUCTURE OF VALUE ORIENTATION OF THE PERSONALITY OF HIGHER EDUCATION STUDENTS WHILE STUDYING PHYSICAL EDUCATION - Головченко, Олексій (SWorldJournal, 2025)
In order to determine the structure of the value orientation of the personality of higher education students while studying physical education, a study was conducted using the adapted methodology of M. Rokich. The structure of value orientations of highe